Aluminium Alloy AA6060 Surface Treatment with High Temperature Steam Containing Chemical Additives. (2015) - Din, Rameez Ud; Tabrizian, Naja; Jellesen, Morten S.; Ambat, Rajan
Abstract: The steam treatment process was employed to produce a conversion coating on aluminium alloy AA6060. The changes in microstructure and its effect on corrosion resistance properties were investigated. Various concentrations of KMnO4 containing Ce(NO3)3 was injected into the steam and its effect on the formation of steam-based conversion coating was evaluated. The use of Mn-Ce into the steam resulted in incorporation of these species into the conversion coating, which resulted in improved corrosion resistance of the alloy substrate.